Professionals' perspectives on how to address persistent oral health inequality among young children: an exploratory multi-stakeholder analysis in a disadvantaged neighbourhood of Amsterdam, the Netherlands - Awani Balasooriyan; Christine Dedding; Clarissa Calil Bonifácio; Monique H. van der Veen (BMC, 2022)
Abstract Background Oral health promotion interventions have had limited success in reaching families in disadvantaged neighbourhoods resulting in persistent oral health inequality. This qualitative study provides insight into professionals' perspectives on children's poor oral health (≤ 4 years), their perceptions of the roles and responsibilities, and opportunities for child oral health promotion strategies. Methods Thirty-Eight professionals from different domains (community, social welfare, general health, dental care, public health, private sector) working in a disadvantaged neighbourhood in Amsterdam, the Netherlands, participated through 24 semi-structured (group) interviews. Transcripts and notes were analysed through thematic analysis. Results Professionals indicate that unhealthy diet, children's non-compliance, poor parental coping, parental low oral health literacy, parent's negative attitude, family's daily struggles, and insufficient emphasis on childhood caries prevention in dental practices, general healthcare and social welfare organisations, underlie poor oral health. They hold parents most responsible for improving young children's oral health, but recognise that families' vulnerable living circumstances and lack of social support are important barriers. Interestingly, non-dental professionals acknowledge their beneficial role in child oral health promotion, and dental professionals stress the need for more collaboration. Conclusion A broad child-, parental-, and societal-centred educational communication strategy is perceived as promising. Professionals working within and outside the dental sector acknowledge that local and collective action is needed. This involves a better understanding of family's complex daily reality. Furthermore, intensifying child oral health knowledge in dental practices is essential in collaboration with families, general health and social welfare organisations.